Efficient transposition of the youngest miniature inverted repeat transposable element family of yellow fever mosquito in yeast. (8th April 2015) - Fattash, Isam; Lee, Chia‐Ni; Mo, Kaiguo; Yang, Guojun
<x xml:space="preserve">Abstract</x> Miniature inverted repeat transposable elements (MITEs) are often the most numerous DNA transposons in plant and animal genomes. The dramatic amplification of MITE families during evolution is puzzling, because the transposase sources for the vast majority of MITE families are unknown. The yellow fever mosquito genome contains > 220‐Mb MITE sequences; however, transposition activity has not been demonstrated for any of the MITE families. The Gnome elements are the youngest MITE family in this genome, with at least 116 identical copies. To test whether the putative autonomous element Ozma is capable of mobilizing Gnome and its two sibling MITEs, analyses were performed in a yeast transposition assay system. Whereas the wild‐type transposase resulted in very low transposition activity, mutations in the region containing a putative nuclear export signal motif resulted in a dramatic (at least 4160‐fold) increase in transposition frequency. We have also demonstrated that each residue of the novel DD37E motif is required for the activity of the Ozma transposase. Footprint sequences left at the donor sites suggest that the transposase may cleave between the second and the third nucleotides from the 5' ends of the elements. The excised elements reinsert specifically at dinucleotide 'TA', ~ 55% of them in yeast genes. The elements described in this article could potentially be useful as genetic tools for genetic manipulation of mosquitoes.